The Connection Between Rap1 and Talin1 in the Activation of Integrins in Blood Cells - Sun, Hao; Lagarrigue, Frederic; Ginsberg, Mark H. (Frontiers in Cell and Developmental Biology, 2022)
Integrins regulate the adhesion and migration of blood cells to ensure the proper positioning of immune cells in the context of the local microenvironment. They detect physical/chemical stimulus in the extracellular matrix and regulate signaling pathways in blood cells to mediate their function. Integrins are usually in a resting state in blood cells until agonist stimulates a high-affinity conformation, which is a key step in the traffic and functions of blood cells and defined as "integrin activation". In this review, we summarize recent findings in understanding the mechanisms of integrin activation in blood cells. We focus on recent advances in signaling events that involve Rap1 regulating the talin1-integrin interaction and the resulting integrin activation in lymphocytes, platelets, and neutrophils.